Rain water reuse in the production of non-structural concrete blocks - Oliveira, João Paulo Gama de; Silva, Luana Celeste; Fernandes, Fernando A. da S.; Paz, Lidiane Andrade Fonseca da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Water is essential in all spheres of human life. Among them the construction. Not considered as a building material, water is consumed on a large scale in construction sites, concrete producers and the production of concrete blocks. Clever use and sustainable alternatives reduce consumption and combine progress and cleaner production. The reuse of rainwater proved to be an effective and profitable solution to a factory of non-structural concrete blocks in the city of Palmas in Tocantins state. The water collected and stored for this purpose was subjected to studies that first stage showed the presence of foreign bodies. These irregularities detected through screens and filters to eliminate foreign bodies and made water itself to manufacture. Studies have ensured water quality, capable of producing without interference blocks on their properties. The result was productive feasibility, cost reduction and sustainable production.